"The Anxiety of Influence": Rashbam's Approach to Rashi's Commentary on the Torah. Issue 2 (23rd November 2016) - Viezel, Eran
Abstract : Rashbam's approach to Rashi's commentary on the Torah is characterized by contrasts: originality and continuity, independence and dependence, open admiration and flagrant aggression. Scholars have clarified various aspects of this complex stance, yet their analyses do not provide a comprehensive explanation for it. This article argues that Rashbam's approach to Rashi's commentary is not based on methodological principles alone, but also includes an emotional element that is in part unconscious. To analyze these complex emotional elements of the text, the article uses a theoretical model that demonstrates that the ambivalence reflected in the text is not unusual, and in fact can be found in relationships between other writers— "the anxiety of influence, " as formulated by Harold Bloom. This conclusion sheds new light on Rashbam's commentary, including several of its more well-known passages.